Applications of piezoelectric biomaterials in dental treatments: A review of recent advancements and future prospects - Kaichen Zeng; Yifan Lin; Shirong Liu; Ziyan Wang; Lvhua Guo (Materials Today Bio)
Piezoelectric biomaterials have attracted considerable attention in dental medicine due to their unique ability to convert mechanical force into electricity and catalyze reactions. These materials demonstrate biocompatibility, high bioactivity, and stability, making them suitable for applications such as tissue regeneration, caries prevention, and periodontal disease treatment. Despite their significant potential, the clinical application of these materials in treating oral diseases remains limited, facing numerous challenges in clinical translation. Therefore, further research and data are crucial to advance their application in dentistry. The review emphasizes the transformative impact of multifunctional piezoelectric biomaterials on enhancing dental therapies and outlines future directions for their integration into oral healthcare practices.